Effects of productivity growth on domestic savings across countries: Disentangling the roles of trend and cycle - Abhishek Kumar; Sushanta Kumar Mallick; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Resource mobilization continues to be an important policy challenge for developing economies, raising questions as to what determines differences in saving behaviour across countries. Using a panel of 47 economies with at least 40 years of continuous time series data, we causally identify, using a range of approaches, that higher productivity growth leads to greater savings, thereby contributing to higher investment. The dynamics of such productivity shocks have been disentangled into trend and cyclical shocks to uncover that cyclical productivity shocks tend to have a strong positive effect on saving rates. Comparing two countries with different levels of productivity (high and low) in a counterfactual analysis, this result remains robust, and we reconfirm that large declines in productivity shocks were associated with large decline in saving rates. Countries should focus on promoting policies to boost productivity growth and thereby achieve higher savings instead of focusing on savings-induced policies alone.
Keywords: E21; E22; E32; E60; 330; saving; productivity growth; trend shock; cyclical shock; causal identification